Nutritional composition of human milk and its association with maternal and perinatal factors - Daniele Marano; Raquel Ximenes Melo; Danielle Aparecida da Silva; Marina Machado Vilarim; Maria Elisabeth Lopes Moreira (Sociedade de Pediatria de São Paulo, 2023)
ABSTRACT Objective: The objective of this study was to evaluate the influence of maternal and perinatal factors on the nutritional composition of human milk. Methods: A cross-sectional study was conducted between November 2018 and January 2020, with 181 donors selected in Tertiary Health Units of the Unified Health System - from one collection station and five Human Milk Banks. Data were collected through a standardized questionnaire. To be fit to be a donor in a Human Milk Banks and produce mature milk were the eligibility criteria to participate in the study. We excluded milk samples with Dornic acidity above 8° D. The dependent variables were the macronutrients of human milk (i.e., carbohydrates, proteins, lipids, and total energy), that were analyzed using spectroscopy with the Miris Human Milk Analyzer™. The maternal and perinatal factors were the independent variables. Results: Women with pre-gestational obesity and gestational weight gain above the recommendation showed a lower protein concentration compared to eutrophic women (median=0.8, interquartile range (IQR): 0.7-0.9 vs. median=0.8, and IQR: 0.8-1.0) and those with adequate gestational weight gain (median=0.8, IQR: 0.7-0.9 vs. median=0.9, and IQR: 0.8-1.0), respectively. The other analyzed factors (i.e., maternal habits, comorbidities, and perinatal factors) were not associated with the nutritional composition of human milk. Conclusions: The assessment of factors associated with the nutritional composition of human milk is extremely important to assist postpartum care. Pre-gestational obesity and inadequate gestational weight gain were the only factors statistically associated with the nutritional composition of human milk as they impacted its protein content.